Impact of LULUCF accounting rules for climate change mitigation goals: winning or losing? - Kazanavičiūtė, Vaiva; Dagiliūtė, Renata (Journal of Environmental Engineering and Landscape Management, 2023)
Land use, land-use change, and forestry (LULUCF) sector plays an important role in climate change mitigation as long-term goal of carbon neutral economy depends on sector’s ability to sequestrate carbon in biomass and soil. With reference to the Paris Agreement, accounting rules for LULUCF sector have been heavily discussed in European Union (EU), seeking of trustworthy inclusion of the sector in the assessment of Union’s greenhouse gas (GHG) emission reduction target. Therefore, the paper aims to analyze LULUCF sector’s contribution to climate change mitigation with different accounting rules applied in EU countries and particularly in Lithuania. On EU level LULUCF sector’s absorption in 2019 has equaled around –234 million t CO2 eq. (6% of total EU GHG emissions), in some countries reaching more than a half of national emissions. However, different accounting rules applied may provide significantly different number of potential credits for separate EU countries, creating some “winners” and “losers” situation. Though inclusion of LULUCF sector into GHG’s emissions reduction targets remains discussible, some stability in rules is one of the main preconditions for proper LULUCF sector management decisions.